Digital preservation of Ukrainian audiovisual heritage during wartime: challenges and institutional practices - Kovalenko, Yuliia (Latvian Academy of Culture, 2025)
This article is dedicated to investigating the impact of the war in Ukraine (Russian-Ukrainian War, from 2014, full-scale invasion – 2022) on the preservation of audiovisual heritage and the documentation of wartime events. The study focuses on the role of digital technologies in safeguarding cultural identity, recording historical events, and addressing challenges Ukrainian archives face during the ongoing conflict. It examines the practices of digitization and archiving by state and civic institutions, including the Central State Archive of Film, Photo, and Audio Documents named after Pshenychnyi, the Dovzhenko Centre, and the Center for Urban History in Lviv. The research highlights the implementation of international archiving standards, innovative technologies, and ethical considerations, particularly in documenting war crimes. Results demonstrate how digital archives preserve historical memory, foster humanitarian awareness, and facilitate global cultural exchange. The article concludes with recommendations for enhancing Ukraine’s digital preservation framework, emphasizing collaboration with global organizations, adopting advanced technologies, and aligning with international standards to safeguard cultural heritage long-term.
Keywords: digital preservation; audiovisual heritage; wartime archives; archival standards; historical memory